VALIDITY OF COLOR DOPPLER SONOGRAPHY IN EVALUATION OF MALIGNANT PORTAL VEIN THROMBOSIS IN HEPATOCELLULAR CARCINOMA - Alam, Shahjehan; Pervez, Rayyan; Rafique, Salman (Journal of Postgraduate Medical Institute, 2013)
Objective: The objective of this study was to assess the validity of color doppler sonography in theevaluation of malignant portal vein thrombosis in hepatocellular carcinoma (findings on biphasic spiralcomputed tomography were used as the gold standard). Methodology: This study was conducted in the Department of Diagnostic and Interventional Radiology at Shifa International Hospital, Islamabad from March 2009 to November 2009. A total of 100 patients thosewho were already diagnosed cases of HCC or those having high suspicion of HCC based on clinicalcriteria (e.g., chronic hepatitis B or C, liver cirrhosis, increased alpha fetoprotein level [>400ng/dl]) and /or Imaging findings (e.g., sonography, MRI, CT) were included in this study. Results: Color doppler sonography had 80.7% sensitivity and 100% specificity in the detection of arterialflow in the portal vein thrombus (i.e., malignant thrombus) in comparison with biphasic CT (taken as goldstandard). Conclusion: Color doppler sonography is an effective, noninvasive method for evaluating the presence ofmalignant portal vein thrombosis associated with HCC.